Failure Analysis of Perforation in 3003 Aluminum Tubes Used in Automotive Air Conditioning - YANG Shuyu, ZHU Ranran, QIAN Weifeng, HAN Yi, LIU Zhenshan, LI Xiulei (Cailiao Baohu, 2024)
In order to study and analyze the causes of perforation failure in 3003 aluminum tubes， used in automobile air conditioning， the reasons for surface perforation defects in these tubes were investigated.This investigation involved macro-morphology analysis，chemical composition analysis， scanning electron microscope micro-morphology analysis and energy spectrum analysis.Results showed that nonmetallic inclusions on the surfaces of the 3003 aluminum tubes damaged the integrity and continuity of these surfaces.This issue prevented the formation of a dense oxide film at the inclusion sites.Under the combined influence of the strongly corrosive elements chlorine (Cl) and sulfur (S)， pitting and perforation failures occurred in the 3003 aluminum tubes.It was suggested that the addition of refining agents should be carefully controlled during the melting process of the 3003 alloy.Additionally， improvements in the filtering of inclusions in the aluminum liquid， as well as enhancements in the surface cleanliness and storage environment of the aluminum tubes， were recommended.These research findings could provide a certain reference for the manufacturing of 3003 aluminum tubes.